CORRELATION OF WEIGHT REDUCTION TO THE QUALITY OF SMOKED MACKEREL (Euthynnus affinis) FILLET STORED IN COLD TEMPERATURE(7 ± 2 °C) - Elisabet Sancti Yudiandani; Sukirno Mus; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in March until April 2015 to determine the correlation of weight reduction by smoking to the quality of smoked mackerel (Euthynnus affinis) fillet that stored at chilling temperature (7 ± 2 °C). The research was using correlational-experimental method. The first step is filleting the fish at the size of 1.5 cm in thickness and 70 g in weight, then soaked it in 30% salt brine for 5 minutes. Then the fillet was soaked in the liquid smoke at the consentration of 8% for an hour and then dried until the weight was reducing until several percentages, namely: 0%, 20%, 40% and 60% from the initial weight. Parameters used were hedonic values (appearance, odor, taste and texture), moisture content, pH, free fatty acid, total phenol, and bacterial total plate counts. The data obtained were tabulated and analyzed using simple linear regression. The result shows that the increase of weight reduction on smoked fillet mackerel stored in chilling temperature (7 ± 2 °C) was significantly correlated to the increase of hedonic values (appearance (R2=0.665), odor (R2=0.629), taste (R2=0.559), and texture (R2=0.763)), total phenol (the first total phenol (R2=0.868), the end total phenol (R2=0.940) and free fatty acid (R2=0.493) (p<0.05). Otherwise, it was significantly correlated to the decrease of moisture content (R2=0.902), pH (R2=0.339) and bacterial total plate counts (R2=0.260) (p<0.05).Keywords: chilling temperature, Euthynnus affinis, smoked fish, weight reduction